Penggunaan Media Pembelajaran Digital Berbasis Game Edukatif Pada Mata Pelajaran Rekayasa Perangkat Lunak Kelas XI SMK Negeri 6 Kendari - Syamrin, Andika; Sabara, Ummu Nurfadhillah; Septiani, Mitha; Pratiwi, Tiara Nur; Yamin, Muhammad Rajun Akmal; D, Darman (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This community service program aims to improve the quality of learning, learning motivation, student engagement, and learning outcomes of Grade XI Software Engineering (RPL) students at SMK Negeri 6 Kendari through the use of educational game-based digital learning media using the Zep Quiz platform. The main problems faced by the partner school include low student participation in learning, low learning motivation, and limited use of interactive digital learning media that align with the characteristics of digital-native students. The implementation method consisted of several stages, including needs analysis, digital learning media design, student training, classroom mentoring, and evaluation. Zep Quiz was used as an interactive learning medium for basic programming and algorithmic logic topics in the RPL subject. The results showed a significant improvement in students’ learning motivation, classroom engagement, and conceptual understanding of basic RPL materials. Students demonstrated more positive learning attitudes, higher enthusiasm, and greater active involvement in digital-based learning activities. This program confirms that educational game-based digital learning media can create a more engaging, interactive, and effective learning environment, contributing significantly to the improvement of vocational education quality. Therefore, the use of Zep Quiz is recommended as an alternative digital learning medium in vocational schools, particularly in Software Engineering programs.